Written Law and Interpretation, According to Gény - Velásquez Villamar, Gastón Alexander (Ius Humani. Jornal do direito, 2021)
The objective of this article is to understand the relationship between written law and the interpretation of the terms proposed by FranÃ§ois Gény, taking into account his description of the interpretive phenomenon and the elements of its rationality. This paper is strictly referred to his work titled " Method of Interpretation and Sources in Positive Private Law", from which we establish the notions of law, interpretation, and rationality that the author developed, as well as his main ideas on extensive interpretation, analogy, the logical rules and the cases in which the elements extrinsic to the written law that can be considered in the practice of interpretation. We will finish by considering some references by the author to the method of free scientific research, such as his reflections on the limits of the interpretation dissociated from the will of the legislator. This article responds to a theoretical investigation, whose source is printed texts, therefore the methodology used required analytical synthetic and historical-logical methods. As a content analysis method, the textual analysis of the documents considered in the research has been used.